Effect Of Flavoring On The Organoleptic Of Local Variety Soya Juice - Susanti, Ambar; Nasrulloh, Basharudin; Chusnah, Miftachul (AGARICUS: Advances Agriculture Science & Farming, 2024)
The aim of the research was to determine the effect of adding sugar and flavoring at different shelf lives on the organoleptic characteristics of local varieties of soybean juice. The research was carried out from November 2023 to January 2024 in Brangkal Village, Jombang Regency and the Faculty of Agriculture KH. Abdul Wahab Hasbullah University. The treatment used are ; 1) B0J1 = soybean juice stored 1 hour after cooking, 2) B0J6 = soybean juice stored 6 hours after cooking, 3) B1J1 = soybean juice + granulated sugar stored 1 hour, 4) B1J6 = soybean juice + granulated sugar stored 6 hours after cooking, 5) B2J1 = soybean juice + strawberry flavoring, storage 1 hour after cooking, and B2J6 = soybean juice + strawberry flavoring, storage 6 hours after cooking. This research used an experimental method with a completely randomized design with one factor which was repeated three times. The sample in this study was soybean juice which was used in hedonic tests and the shelf life of it with 15 panelists. Data analysis used ANOVA with a further BNT test at the 5% level. It is known that the color of soybean juice and granulated sugar stored 6 hours after cooking was more favorable compared to the other 7 treatments. Soybean juice without added sugar or flavorings, with storage 1 and 6 hours after cooking, and soybean juice and sugar with storage 6 hours after cooking had the most favorable taste compared to the other 5 treatments